FACTORS AFFECTING DIVIDEND POLICY ON LQ45 INDEX COMPANIES ON THE INDONESIA STOCK EXCHANGE - Ardelia, Janice; Lukman, Hendro (International Journal of Application on Economics and Business, 2023)
Dividends are one of the considerations in stock investment. The purpose of this study is to analyze the effect of “Board Size, Board Independence, “Management Ownership”, Institutional Ownership, and “Collateral Assets” on the “Dividend Policy”. This study uses 17 samples of public companies that are part of the LQ45 Index with 84 data observation during 2016-2020. The sampling method used purposive sampling technique. data analysis using multiple regression analysis where data is processed using IBM SPP Statistic Version 25.0 software. The results show that “Management Ownership” and “Collateral Assets” have a positive and significant effect on “Dividend Policy”. Meanwhile, “Board Size”, “Board Independence”, and “Institutional Ownership” have no significant effect on “Dividend Policy”. The implication of this research is that there is a need for Institutional Ownership representatives on the company's “Board of Directors” in order to influence the companies’ “Dividend Policy” and provide a good signal for investors.